2022
DOI: 10.1186/s12954-022-00648-y
|View full text |Cite
|
Sign up to set email alerts
|

Food as harm reduction during a drinking session: reducing the harm or normalising harmful use of alcohol? A qualitative comparative analysis of alcohol industry and non-alcohol industry-funded guidance

Abstract: Background The aim of this study was to critically analyse information concerning the relationship between alcohol and food consumption provided via alcohol industry (AI) funded and non-AI-funded health-oriented websites, to determine the role it plays within the alcohol information space, and how this serves the interests of the disseminating organisations. Methods Information on food as a harm reduction measure while drinking alcohol was extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The ways in which corporations shape preferences for products and influence perceptions about their health-related risks was another major topic of the included articles. Corporations were accused of promoting excessive consumption of harmful products, for example, by engaging in intensive and highly-resourced marketing campaigns that normalize their consumption (e.g., portraying alcohol as part of a normal everyday routine [84]) [12,18,36,42,47,51,63,65,7274,8499]. They were reported to influence the public debate about product related-risks by reframing and creating uncertainty about the causes of health issues (e.g., focusing on genetic causes of cancer as opposed to alcohol consumption [100]) [18,20,27,28,31,32,34,36,37,4042,44,46,48,5052,5658,64,65,75,76,79,81,101104] and acquiring or funding media companies, making it more difficult for public health messages to be heard [20,45,48,49,65,72].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ways in which corporations shape preferences for products and influence perceptions about their health-related risks was another major topic of the included articles. Corporations were accused of promoting excessive consumption of harmful products, for example, by engaging in intensive and highly-resourced marketing campaigns that normalize their consumption (e.g., portraying alcohol as part of a normal everyday routine [84]) [12,18,36,42,47,51,63,65,7274,8499]. They were reported to influence the public debate about product related-risks by reframing and creating uncertainty about the causes of health issues (e.g., focusing on genetic causes of cancer as opposed to alcohol consumption [100]) [18,20,27,28,31,32,34,36,37,4042,44,46,48,5052,5658,64,65,75,76,79,81,101104] and acquiring or funding media companies, making it more difficult for public health messages to be heard [20,45,48,49,65,72].…”
Section: Resultsmentioning
confidence: 99%
“…They were reported to influence the public debate about product related-risks by reframing and creating uncertainty about the causes of health issues (e.g., focusing on genetic causes of cancer as opposed to alcohol consumption [100]) [18,20,27,28,31,32,34,36,37,4042,44,46,48,5052,5658,64,65,75,76,79,81,101104] and acquiring or funding media companies, making it more difficult for public health messages to be heard [20,45,48,49,65,72]. Though commercial entities promoted education as the solution to managing health-related risks [20,45,51,58,66,68,74,80], they were also accused of attempting to shape the public’s understanding of health issues by providing educational resources that promoted their products and/or downplayed the associated health risks (e.g., alcohol [61,62]) [19,20,36,51,63,65,68,80,84,100].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly reported frameworks employed were Mialon and colleagues' framework to monitor the corporate political activity of the food industry [41] (5/37, 14%) and the policy dystopia model [42] and its adaptation to the food industry [43] (the latter is an updated version of Mialon and colleagues' CPA framework) (7/37, 19%). The findings from these studies often revealed the diverse, yet oft-repeated mechanisms through which corporation's advance their interests in ways that can harm population health (e.g., use of messaging to normalize harmful commodity use [44,45]).…”
Section: Plos Onementioning
confidence: 99%